Designing a Digital Literacy Module for Future Elementary Teachers: A UTAUT-Based Needs Approach - Rahmat Syah; Daddy Darmawan (Edukasi, 2026)
This study aims to develop a digital literacy module for prospective elementary school teachers at STABN Sriwijaya, Indonesia, using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework and the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research addresses the urgent need to improve digital literacy among Indonesian teachers, as national competency assessments reveal significant gaps in their ability to integrate technology into pedagogy. A mixed-methods approach was employed, combining surveys, focus group discussions, and expert validation to identify critical needs, including cybersecurity, digital ethics, interactive content creation, and AI-driven tools. The module was designed through iterative phases, emphasizing performance expectancy, effort expectancy, social influence, and facilitating conditions. Validation by multidisciplinary experts confirmed high content validity (CVR >0.75), particularly in alignment with UNESCO standards and practical applicability. Implementation trials with 45 prospective teachers demonstrated significant improvements in digital competency, with 93.3% of participants successfully designing technology-based teaching materials and 88.9% reporting increased confidence in digital tool usage. However, challenges such as limited internet access in rural areas (37% of participants) and gaps in integrating cutting-edge technologies (e.g., AI, VR/AR) were identified. The study concludes that a UTAUT-guided, participatory module design effectively enhances teachers’ readiness for digital education. Recommendations include periodic content updates, infrastructure strengthening, and gamification strategies to ensure sustainability. This research contributes a scalable model for teacher education institutions seeking to address 21st-century digital literacy demands while balancing pedagogical innovation and ethical considerations.